Service legal relations: international legal and administrative-criminal aspect - Leheza, Yevhen; Vlasenko, Denys; Shcherbyna, Yevhen; Moroz, Vita (DIXI, 2023)
The research is devoted to the coverage of international legal acts and standards in European and international practice for the provision of public services as a direction of reforming legal education in Ukraine. Review of materials and methods is performed on the basis of analyzing documentary materials on regulation of the ser-vice legal relations. The directions of improving domestic legislation on the provision of public services taking into account international legal standards are proposed: 1) the development of the theory of public services, which consists in consolidating conceptual and categorical provisions in the concept of public services, prin-ciples of public services, quality criteria for the provision of public services, etc.; 2) unification of the legal re-gulation of administrative procedures by adopting the Administrative Procedure Code of Ukraine, which would clearly disclose the issue of providing public services; 3) fixing in the legal acts the types of legal guarantees to ensure the legality of the provision of public services: monitoring the activities of public administration entities on the provision of public services; 4) holding public servants accountable for refusing to provide a certain type of public service; 5) bringing into line with European experience the requirements for adoption, amendment, cancellation, and the possibility of appealing individual administrative acts that are the results of the provision of public services; vi) decentralization of power, which consists in justifying an increase in the powers of local authorities in comparison with public authorities.
Keywords: accessibility; education; legal education public service; service; transparency; administrative service